New insights into the expression profile of MicroRNA-34c and P53 in infertile men spermatozoa and testicular tissue - Rahbar, S.; Novin, M. G.; Alizadeh, E.; Shahnazi, V.; Pashaei-Asl, F.; AsrBadr, Y. A.; Farzadi, L.; Ebrahimie, E.; Pashaiasl, M. (Cellular and Molecular Biology, 2017)
Spermatogenesis is proliferation and differentiation processes of stem spermatogonia into mature spermatozoa controlled by the genes responsible for transcription and post transcription levels. MicroRNAs (miRNA) are the key factors during gene expression in RNA silencing and post-transcriptional regulation. They play main roles in regulation of early and late spermatogenesis, and reproduction. In this study, we investigate the role of miRNAs in infertile males. The patients were assigned to five groups based on semen analysis (n=55), including normozoospermic (N), moderate oligoasthenoteratozoospermic (MOAT), severe oligoasthenoteratozoospermic (SOAT), obstructive azoospermia (OA) and non-obstructive azoospermia (NOA). Quantitative RT-PCR was recruited to study the expression of miR-34c and tumor suppressor p53 gene. In addition, malondialdehyde (MDA) and DNA fragmentation was measured. Network analysis was performed using Pathway Studio web tool (Elsevier). Our results revealed statistically significant increased expression of miR-34c in moderate oligoasthenoteratozoospermic, non-obstructive azoospermia and an increased expression of p53 in MOAT, SOAT and NOA males. Also, the percentage of DNA fragmentation and oxidative stress was significantly higher in infertile groups (MOAT and SOAT) than other groups. These findings provide a novel molecular mechanism of gene regulation during cell-cycle and apoptosis in sperm, which gives a new regulatory insight into male infertility in terms of molecular diagnosis.